Transfer Teknologi Produksi Natural Soap-Base untuk Kreasi Sabun Suvenir - Ari Asnani; Eva Vaulina Yulistia Delsy; Hartiwi Diastuti (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2019)
ABSTRACT             IPTEKS-based community service has been done with the Entrepreneurship and Workshop unit of MAN Purbalingga. The objectives of the activities were (1) Transferring of soap making technology to produce natural soap-base; (2) Transferring of cold-process and hot-process methods for the creation of soap-souvenirs with various shapes and colors; and (3) Transferring the packaging knowledge for souvenir soap products. The methods applied include student education, training, and the diffusion of science and technology to produce souvenir soap. The post-test results showed that there was an increased knowledge of the partners on saponification reactions (0% to 50%), soap making principles (0% to 54.2%), as well as the understanding of raw materials, additives, and soap-making equipment. The three main factors that could encourage the partners to make soap were an eagerness on how to make soap (70.8%); business opportunity (62.5%), and wanted to make soap creations (29.1%). This community service activity was expected to provide benefits in the form of partnership ability to produce souvenir soap made from natural ingredients with various shapes and colors. Keywords: cold-process, hot-process, souvenir soap